A normative study of auditory perception in Mandarin-speaking children with categories of auditory Performance-II. (June 2021) - Xu, Tianqiu; Zhong, Yan; Wang, Hong; Chen, Xueqing
Abstract: Objective: The aim of this study is to investigate the development of auditory skills in Mandarin-speaking children with normal hearing using CAP-II, and to establish the baseline data for evaluating the auditory performance of children with hearing loss on which designs of appropriate hearing rehabilitation programs can be based. Materials and methods: A total of 223 children participated in this study of which 200 children aged from 1 to 60 months were finally included. Their normal hearing was confirmed by examination of hearing history and high-risk registers for hearing loss, as well as by hearing screening. All children were divided into 10 groups with 20 children in each group based on age. The CAP-II scale was administered to evaluate their development of auditory skills. Results: The categories of auditory performance scores of children with normal hearing improved with their age, the best-fit regression function for prediction of scores from age was Score = 0.94 × ln (age) + 0.08 × (age) + 1.16 and prediction of age from score was Age = 0.65 × (score) 2 –0.14 × (score)–0.23. The overall CAP-II scale exhibited good reliability and validity. Conclusions: and Significance: An improvement in auditory skill with age in children with normal hearing was observed. Ceiling performance in auditory skills was found at the age of 51 months for normal children. A conversion table between age and scores obtained from the data of this study can be used as a reference for the assessment of clinical hearing ability in children.